Student Perceptions of Fraud and Whistleblowing Based on Gender: (Case Study on the Students of Faculty of Economics Universitas Hasyim Asy'ri Tebuireng Jombang) - Rachma Agustina; Dwi Ari Pertiwi; Ika Zutiasari; Meta Ardiana (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2019)
When giant companies are involved in fraud that has an extremely detrimental effect on the economy, the fraud cases become scandalous. The giant company's fraud case was revealed, mostly because of the information within the company that was revealed by the company's employees, which is called whistleblowing. The purpose of this study is to prove the differences in students' perceptions of fraud and whistleblowing behavior based on gender factors. Research is conducted on students of the Faculty of Economics of Universitas Hasyim Asy'ari Tebuireng Jombang, who are in the third semester or above so that they already understand fraud and whistleblowing. This type of research is quantitative research based on empirical studies. The research sample was selected by using the technique of probability sampling with the category of simple random sampling. The hypothesis testing using multiple research paradigms with one dummy variable and two dependent variables so that it uses two simple dummy regression tests. The decision on the results of hypothesis testing uses two R Square determination coefficients to explain the relationship of each variable. The results of this study prove that there is no gender effect on the students' perception of fraud and whistleblowing.